Nanometer lanthanum oxide-carbon fiber-boron nitride synergistically modified silicone rubber and preparation method thereof
By synergistic modification of silicone rubber with nano-lanthanum oxide, carbon fiber, and boron nitride, combined with plasma pretreatment, the performance deficiencies of existing silicone rubber materials have been solved, achieving comprehensive performance improvement and environmental enhancement of automotive piping materials.
Patent Information
- Application Number
- CN202610278738.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-03-09
- Publication Date
- 2026-11-03
- Estimated Expiration
- 2046-03-09
AI Technical Summary
Existing silicone rubber materials have problems such as low mechanical strength, insufficient thermal conductivity, and easy aging and degradation in critical automotive pipelines. Furthermore, traditional modification methods have performance shortcomings and environmental hazards, making it difficult to meet the stringent operating conditions of modern automotive pipelines.
By using ternary synergistic modification of silicone rubber with nano-lanthanum oxide, carbon fiber, and boron nitride, combined with plasma pretreatment, the preparation process is optimized to form a dense composite material, which improves the material's mechanical strength, thermal stability, and environmental friendliness.
It achieves comprehensive performance improvement of materials, adapts to wide temperature range working conditions, meets the usage requirements of key automotive pipelines, and conforms to the trend of green development.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] This invention belongs to the field of rubber composite material technology, and in particular relates to a nano-lanthanum oxide-carbon fiber-boron nitride synergistic modification silicone rubber and its preparation method. Background Technology
[0002] As the automotive industry moves towards higher performance and reliability, the working environments of key components such as fuel hoses, intercooler hoses, and air conditioning hoses are becoming increasingly harsh. These hoses not only need to withstand the corrosive effects of fuel and refrigerants over long periods, but also need to operate in a wide temperature range from -40℃ to over 150℃. This places extremely high demands on the materials' mechanical strength, thermal stability, aging resistance, and barrier properties. Silicone rubber, due to its excellent high and low temperature resistance, weather resistance, and chemical stability, has become the core substrate for manufacturing these automotive hoses. Among them, methyl vinyl silicone rubber, with its moderate crosslinking activity and mechanical properties, is widely used in related fields.
[0003] However, pure silicone rubber has inherent defects such as low mechanical strength, insufficient thermal conductivity, and susceptibility to aging and degradation under long-term high temperatures, making it difficult to fully meet the requirements of critical pipelines in modern automobiles. In existing technologies, researchers often modify silicone rubber using single fillers or binary composite fillers, such as adding carbon fibers to improve mechanical strength, introducing boron nitride to improve thermal conductivity, and adding metal oxides to enhance aging resistance. However, single-modification systems often have performance limitations, while simple binary composite modifications often suffer from uneven filler dispersion and poor interfacial compatibility, resulting in unsatisfactory modification effects and difficulty in achieving synergistic improvements in mechanical properties, heat resistance, and aging resistance. Furthermore, some modification schemes employ simple filler pretreatment processes, further exacerbating filler agglomeration and affecting the overall performance stability of the composite material.
[0004] Meanwhile, there is still room for improvement in the environmental friendliness and long-term service reliability of existing silicone rubber materials for automotive hoses. Some components used in traditional modification processes, such as plasticizers and processing aids, pose environmental risks. Furthermore, after long-term contact with fuel and exposure to wide temperature range cycling, the materials are prone to mechanical property degradation, aging, and cracking, which seriously affect the service life of the hoses and driving safety.
[0005] Therefore, developing a silicone rubber composite material that achieves synergistic improvement in mechanical strength, thermal stability, aging resistance, and environmental friendliness through multi-component filler synergistic modification, optimized filler pretreatment process, and selection of environmentally friendly components has become an urgent need to solve the current performance bottleneck of key automotive pipeline materials. Summary of the Invention
[0006] To address the aforementioned technical problems, this invention provides a synergistic modification of silicone rubber using nano-lanthanum oxide, carbon fiber, and boron nitride, and its preparation method. Through the ternary synergistic modification of nano-lanthanum oxide, carbon fiber, and boron nitride, and the optimized preparation process, the high-temperature resistance, mechanical strength, fuel resistance, and low-temperature toughness of the silicone rubber composite material are comprehensively improved. Moreover, the process is controllable and adaptable to industrial production, highly environmentally friendly, and precisely matches the critical operating conditions of automotive hoses.
[0007] The technical solution adopted in this invention is: A nano-lanthanum oxide-carbon fiber-boron nitride synergistic modified silicone rubber composite material, by weight, comprises the following raw material components: 80-100 parts silicone rubber, 2-5 parts nano-lanthanum oxide, 3-8 parts carbon fiber, 4-10 parts boron nitride, 3-8 parts methyl silicone resin, 1.1-1.6 parts vulcanizing agent, 1-3 parts coupling agent, and 5-12 parts environmentally friendly plasticizer.
[0008] Furthermore, the lanthanum oxide nanoparticles have a particle size of 5–50 nm; the carbon fibers have a length of 50–200 μm and a diameter of 5–15 μm; and the boron nitride is hexagonal boron nitride with a particle size of 10–100 nm.
[0009] Furthermore, the silicone rubber is methyl vinyl silicone rubber, with a vinyl content of 0.08% to 0.16% and a number average molecular weight of 580,000 to 620,000.
[0010] Furthermore, the coupling agent is one or both of silane coupling agents and titanate coupling agents; the environmentally friendly plasticizer is one or both of environmentally friendly oil and environmentally friendly silicone oil.
[0011] Further, the vulcanizing agent is one or more of 2,4-dichlorobenzoyl peroxide, di-tert-butyl peroxide, 2,5-dimethyl-2,5-bis(tert-butylperoxy)hexane, and dicumyl peroxide.
[0012] Furthermore, the modified silicone rubber composite material also contains 2 to 3 parts of antioxidant, which is a compound mixture of antioxidant NBC and antioxidant 445 or antioxidant D, and antioxidant NBC accounts for 75 to 95% of the total weight of the antioxidant.
[0013] Furthermore, 2 to 3 parts of processing aids are added, wherein the processing aids are one or two of dispersant L-24 and waxy polyethylene.
[0014] A method for preparing a nano-lanthanum oxide-carbon fiber-boron nitride synergistic modified silicone rubber composite material, characterized by comprising the following steps: (1) Pretreatment: The carbon fiber is plasma treated for 10-30 min, and then mixed with nano lanthanum oxide, boron nitride and coupling agent. The mixture is stirred at 300-500 rpm for 1-2 h at 80-100℃ to obtain the modified filler. (2) Plasticizing: Add silicone rubber to a two-roll mill and plasticize to Mooney viscosity ML(1+4). 100℃ The base adhesive is obtained when the concentration is 40-60. (3) Mixing: Transfer the base rubber into an internal mixer, add modified filler, methyl silicone resin, environmentally friendly plasticizer, antioxidant and / or processing aid. The antioxidant and processing aid are mixed at 120-130℃ and 50-120rpm for 5-8 minutes. Adjust the temperature to 100-105℃ and discharge the material. Pass the material through a two-roll mill 3-4 times, and hang the sheet to dry. After standing for 12 hours, add the vulcanizing agent, control the roller temperature of the two-roll mill to not exceed 60℃, the roller gap to 0.5-1.0mm, pass the material through a two-roll mill 4-5 times, and then cool the sheet. (4) Vulcanization: The compound obtained in step (3) is placed on a two-roll mill for re-milling once, and vulcanized for 10-15 min at 160-180℃ and 10-15MPa to obtain nano lanthanum oxide-carbon fiber-boron nitride synergistic modified silicone rubber composite material.
[0015] Furthermore, in step (1), the power of plasma treatment is 100-300W and the vacuum degree is 0.05-0.09MPa.
[0016] Application of a nano-lanthanum oxide-carbon fiber-boron nitride synergistic modified silicone rubber composite material in the preparation of automotive fuel hoses, automotive intercooler hoses, or automotive air conditioning hoses.
[0017] The advantages and positive effects of this invention are: 1. Synergistic effect of ternary fillers, excellent comprehensive performance: Through ternary synergistic modification of nano lanthanum oxide, carbon fiber and boron nitride, the material’s high temperature resistance, mechanical strength, fuel resistance and low temperature toughness are improved simultaneously, overcoming the performance shortcomings of traditional single / binary modification.
[0018] 2. Optimized and controllable preparation process, suitable for industrial production: Plasma pretreatment improves the compatibility of fillers, and the process parameters throughout the process are precise and controllable. No special equipment is required, and it can be directly connected to existing production lines to ensure product stability and large-scale output.
[0019] 3. Strong environmental adaptability and precise matching of application needs: Environmentally friendly additives are selected to be specifically adapted to the harsh working conditions of key components such as automotive fuel hoses, which is in line with the trend of green development and provides reliable support for high-end automotive piping materials. Detailed Implementation
[0020] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention. The equipment and raw materials used in the following embodiments are all commercially available conventional products, unless otherwise stated.
[0021] Unless otherwise stated, all percentages, proportions, or parts in this document are by weight. A “part by weight” is the basic unit of measurement for the weight ratio of multiple components. One part can represent any unit weight, such as 1g, 1.5g, or 5g, etc.
[0022] I. Implementation Examples (a) Experimental materials Silicone rubber: Methyl vinyl silicone rubber (model VMQ-110), vinyl content 0.12%, number average molecular weight 600,000, purchased from Dow Corning (China) Investment Co., Ltd. Lanthanum oxide nanoparticles: 20 nm in diameter, ≥99.9% purity, purchased from Shanghai Aladdin Biochemical Technology Co., Ltd. Carbon fiber: 100μm in length and 10μm in diameter, purchased from Zhongfu Shenying Carbon Fiber Co., Ltd. Boron nitride: Hexagonal boron nitride, particle size 50nm, purity ≥99.5%, purchased from Qingdao Haina New Materials Co., Ltd.; Methyl silicone resin: Model RSN-6018, silicone resin content ≥98%, purchased from Dow Corning (China) Investment Co., Ltd.; Vulcanizing agent: 2,5-dimethyl-2,5-bis(tert-butylperoxy)hexane (DBPMH), 98% purity, purchased from Jiangsu Qiangsheng Functional Chemical Co., Ltd. Coupling agent: Silane coupling agent KH-560, purchased from Nanjing Shuguang Chemical Group Co., Ltd., and 3-(2,3-epoxypropoxy)propyltrimethoxysilane used in this invention; The titanate coupling agent NDZ-101 was purchased from Nanjing Daoning Chemical Co., Ltd. The one used in this invention is isopropyl triisostearoyl titanate. Environmentally friendly plasticizer: Environmentally friendly silicone oil (model PMX-200, viscosity 100cs), purchased from Dow Corning (China) Investment Co., Ltd.; Environmentally friendly oil (model KN4006) was purchased from China National Petroleum Corporation Karamay Petrochemical Branch. Antioxidants: Antioxidant NBC (98% purity), Antioxidant 445 (99% purity), Antioxidant D (chemical name 2,2'-methylenebis(4-methyl-6-tert-butylphenol), model AO-D-98, purity ≥98%, purchased from Shanghai Shishihewei Chemical Co., Ltd.), among which antioxidants NBC and 445 were purchased from BASF (China) Co., Ltd. Processing aid: Dispersant L-24, purchased from Clariant Chemicals Ltd.; Waxy polyethylene (model PE-W100) was purchased from Shanghai Lianle Chemical Co., Ltd.
[0023] (II) Example 1 Pretreatment: 3g of carbon fiber was subjected to plasma treatment for 20min at a power of 200W and a vacuum of 0.07MPa; then it was mixed with 2g of nano lanthanum oxide, 4g of boron nitride and 1g of silane coupling agent KH-560, placed in a three-necked flask and stirred at 90℃ and 400rpm for 1.5h to obtain the modified filler. Plasticizing: Add 80g of silicone rubber to a two-roll mill and plasticize to Mooney viscosity ML(1+4). 100℃ The value is 50, thus obtaining the base adhesive; Mixing: Transfer the base rubber into an internal mixer, add the above modified filler, 3g methyl silicone resin, and 5g environmentally friendly silicone oil, and mix at 125℃ and 80rpm for 6 minutes. Adjust the temperature to 102℃ and discharge the material. Pass the material through a two-roll mill 3 times, and hang it to dry. After standing for 12 hours, add 1.1g of vulcanizing agent DBPMH, control the two-roll mill roll temperature at 50℃ and the roll gap at 0.8mm, pass the material through a two-roll mill 4 times, and then cool it. Vulcanization: The compound was re-milled once on a two-roll mill and vulcanized for 12 minutes at 170℃ and 12MPa to obtain a nano-lanthanum oxide-carbon fiber-boron nitride synergistic modified silicone rubber composite material.
[0024] (III) Example 2 Pretreatment: 5g of carbon fiber was plasma-treated for 15min at a power of 150W and a vacuum of 0.06MPa. Then it was mixed with a compound of 3g of nano lanthanum oxide, 7g of boron nitride, 2g of silane coupling agent KH-560 and titanate coupling agent NDZ-101 (mass ratio 1:1), placed in a three-necked flask, and stirred at 85℃ and 350rpm for 1.2h to obtain the modified filler. Plasticizing: Add 90g of silicone rubber to a two-roll mill and plasticize to Mooney viscosity ML(1+4). 100℃ The value is 45, and the base adhesive is obtained; Mixing: Transfer the base rubber into an internal mixer, add the above modified filler, 5g methyl silicone resin, 8g of a compound of environmentally friendly silicone oil and environmentally friendly oil (mass ratio 1:1), 2g antioxidant (antioxidant NBC and antioxidant 445 mass ratio 9:1), and 2g processing aid (dispersant L-24 and waxy polyethylene mass ratio 1:1). Mix at 122℃ and 60rpm for 7min, adjust the temperature to 103℃ and discharge. Pass through a two-roll mill 4 times, sheet out and hang to dry. After standing for 12h, add 1.3g vulcanizing agent DBPMH, control the two-roll mill roll temperature at 55℃ and roll gap at 0.6mm, pass through a two-roll mill 5 times, and sheet out and cool. Vulcanization: The compound was re-milled once on a two-roll mill and vulcanized for 13 minutes at 165℃ and 11MPa to obtain a nano-lanthanum oxide-carbon fiber-boron nitride synergistic modified silicone rubber composite material.
[0025] (iv) Example 3 Pretreatment: 8g of carbon fiber was plasma treated for 25min at a power of 250W and a vacuum of 0.08MPa; then it was mixed with 5g of nano lanthanum oxide, 10g of boron nitride and 3g of titanate coupling agent NDZ-101, placed in a three-necked flask and stirred at 95℃ and 450rpm for 1.8h to obtain the modified filler. Plasticizing: Add 100g of silicone rubber to a two-roll mill and plasticize until the Mooney viscosity ML(1+4) is reached. 100℃ The value is 55, thus the base adhesive is obtained; Mixing: Transfer the base rubber into an internal mixer, add the above-mentioned modified filler, 8g of methyl silicone resin, 12g of environmentally friendly oil, 3g of antioxidant (antioxidant NBC to antioxidant 445 mass ratio 19:1), and 3g of processing aid dispersant L-24. Mix at 128℃ and 100rpm for 5 minutes, adjust the temperature to 104℃ and discharge. Pass the mixture through a two-roll mill 3 times, hang the sheet to dry, and let it stand for 12 hours. Then add 1.6g of vulcanizing agent DBPMH, control the two-roll mill roll temperature at 58℃ and the roll gap at 1.0mm, pass the mixture through a two-roll mill 4 times, and then cool the sheet. Vulcanization: The compound was re-milled once on a two-roll mill and vulcanized for 11 min at 175℃ and 14MPa to obtain a nano-lanthanum oxide-carbon fiber-boron nitride synergistic modified silicone rubber composite material.
[0026] (V) Example 4 Pretreatment: 4g of carbon fiber was plasma treated for 20min at a power of 200W and a vacuum of 0.07MPa; then it was mixed with 3g of nano lanthanum oxide, 6g of boron nitride and 2g of silane coupling agent KH-560, placed in a three-necked flask and stirred at 90℃ and 400rpm for 1.5h to obtain the modified filler. Plasticizing: Add 90g of silicone rubber to a two-roll mill and plasticize to Mooney viscosity ML(1+4). 100℃The value is 48, and the base adhesive is obtained; Mixing: Transfer the base rubber into an internal mixer, add the above modified filler, 5g methyl silicone resin, 7g environmentally friendly silicone oil, 2g antioxidant (antioxidant NBC to antioxidant D mass ratio 9:1), and 2g processing aid dispersant L-24. Mix at 125℃ and 70rpm for 6 minutes, adjust the temperature to 103℃ and discharge. Pass the mixture through a two-roll mill 4 times, sheet and hang to dry. After standing for 12 hours, add 1.2g vulcanizing agent DBPMH, control the two-roll mill roll temperature at 52℃ and roll gap at 0.7mm, pass through a two-roll mill 4 times, and sheet and cool. Vulcanization: The compound was re-milled once on a two-roll mill and vulcanized for 12 minutes at 170℃ and 12MPa to obtain a nano-lanthanum oxide-carbon fiber-boron nitride synergistic modified silicone rubber composite material.
[0027] II. Comparative Example (a) Comparative Example 1 The difference from Example 2 is that no nano-lanthanum oxide is added, while the other raw materials, amounts, and preparation processes are the same.
[0028] (ii) Comparative Example 2 The difference from Example 2 is that no carbon fiber is added, while the other raw materials, amounts and preparation processes are the same.
[0029] (iii) Comparative Example 3 The difference from Example 2 is that boron nitride is not added, while the other raw materials, dosages, and preparation processes are the same.
[0030] (iv) Comparative Example 4 The difference from Example 2 is that no methyl silicone resin is added, while the other raw materials, amounts, and preparation processes are the same.
[0031] (v) Comparative Example 5 The difference from Example 2 is that the carbon fiber was not subjected to plasma treatment, while the other raw materials, amounts, and preparation processes are the same.
[0032] (vi) Comparative Example 6 The difference from Example 2 is that the silicone rubber is replaced with ordinary methyl silicone rubber (vinyl content 0.05%, number average molecular weight 500,000), while the other raw materials, dosages and preparation processes are the same.
[0033] (vii) Comparative Example 7 The difference from Example 2 is that the antioxidant is replaced with 2g of a single antioxidant NBC, while the other raw materials, dosages and preparation processes are the same.
[0034] III. Performance Testing (a) Test items and standards Mechanical properties: Tensile strength and elongation at break were tested according to GB / T528-2009. The specimen was dumbbell type 2, and the tensile rate was 500 mm / min. High temperature aging resistance: According to GB / T3512-2014, the sample was placed in a 280℃ hot air aging chamber for 168h and the tensile strength retention rate and elongation at break retention rate were tested after aging. Fuel resistance: The sample was immersed in RON95 automotive gasoline at 23°C for 72 hours, and the volume change rate and tensile strength retention rate after immersion were tested. Low temperature elasticity: According to GB / T5565.2-2017, after placing the sample in a -40℃ low temperature chamber for 2 hours, flatten it by 50% of the outer diameter of the product and observe whether cracks appear. Mooney viscosity: Tested according to GB / T1232.1-2016 ML(1+4) 100℃ .
[0035] (ii) Testing equipment Electronic universal testing machine: CMT6104, METS Industrial Systems (China) Co., Ltd.; Hot air aging chamber: 401A, Shanghai Experimental Instrument Factory Co., Ltd.; Cryogenic Chamber: DW-40, Zhongke Meiling Cryogenic Technology Co., Ltd.; Mooney Viscometer: MV-2000, Beijing Youshen Electronic Instruments Co., Ltd.; Electronic balance: ME204E, Mettler Toledo Instruments (Shanghai) Co., Ltd.
[0036] IV. Test Results Table 1. Results of Basic Machining and Mechanical Property Tests
[0037] Table 2 Results of Environmental Tolerance Performance Tests
[0038] V. Results Analysis 1. Mechanical property analysis: The tensile strength of Examples 1-4 is all above 6.2 MPa, and the elongation at break is all above 315%, significantly better than the comparative examples. Among them: Example 2 (NBC+445 compound antioxidant) and Example 4 (NBC+D compound antioxidant) showed the best performance, with tensile strengths of 6.8MPa and 6.6MPa, and elongation at break of 332% and 328%, respectively, proving that both compound antioxidant systems can synergistically improve mechanical properties with ternary fillers. Comparative Examples 1-3 lacked any of the fillers—nano lanthanum oxide, carbon fiber, or boron nitride—thus failing to form the ternary synergistic effect of 'rigid skeleton (carbon fiber) + dispersion reinforcement (nano lanthanum oxide) + interface regulation (boron nitride),' resulting in a significant decrease in mechanical properties. The compounded antioxidant further improved the tensile strength and elongation of the material by inhibiting free radical degradation during processing. Comparative Example 7 used a single antioxidant, NBC, which lacked a synergistic inhibition effect, and its performance was lower than that of Examples 2 and 4, verifying the synergistic advantages of the compounded antioxidant. Comparative Example 6 had the worst mechanical properties due to insufficient vinyl content and molecular weight of the silicone rubber.
[0039] High-temperature aging resistance analysis: After aging at 280℃ for 168 hours, the tensile strength retention rate of Examples 1-4 was all above 85%, and the elongation at break retention rate was all above 78%. Examples 2 (92.1%, 86.7%) and 4 (90.5%, 84.3%) showed the best aging performance, indicating that the compound systems of antioxidants NBC and 445, and NBC and D, can effectively inhibit the degradation of silicon oxide chains at high temperatures. Comparative Example 4, without the addition of methyl silicone resin, could not form a stable three-dimensional cross-linked network. At high temperatures, the silicon oxide chains were prone to breakage and rearrangement, resulting in severe performance degradation after aging. Comparative Examples 1-3, lacking any synergistic filler, had insufficient thermal conductivity and interfacial stability, leading to a significant decrease in thermal stability. In the compound antioxidant, NBC (metal passivator) and 445 / D (phenolic antioxidant) worked synergistically to block free radical chain reactions, significantly improving thermal stability.
[0040] Fuel resistance analysis: The volume change rate after gasoline immersion in Examples 1-4 was ≤2.1%, and the tensile strength retention rate was ≥82.3%. Examples 2 (1.8%, 88.5%) and 4 (1.9%, 86.8%) showed the best fuel resistance, indicating that the ternary filler and compound antioxidant work synergistically to form a dense barrier layer and reduce fuel penetration. The ternary filler forms a dense interface layer with the silicone rubber matrix, reducing the penetration of fuel molecules. Therefore, the examples exhibit excellent fuel resistance. In contrast, the comparative examples, due to the lack of synergistic effect of the filler or the mismatch of raw materials, have pores and defects at the interface, making it easier for fuel molecules to penetrate, resulting in volume expansion and strength loss, which are more pronounced.
[0041] Low-temperature elasticity analysis: Examples 1-4 and Comparative Examples 1-5 and 7 showed no cracks at -40℃, while only Comparative Example 6 (silicone rubber that did not meet the requirements) showed slight cracks, proving that methyl vinyl silicone rubber, together with ternary fillers and compound antioxidants, can ensure the toughness of the material in a wide temperature range.
[0042] VI. Conclusion Comparative tests of the examples and comparative examples show that the modified silicone rubber composite material prepared by this invention, using methyl vinyl silicone rubber as the matrix and combining it with a ternary synergistic modification system of nano-lanthanum oxide, carbon fiber, and hexagonal boron nitride, along with plasma pretreatment and optimized mixing and vulcanization parameters, exhibits excellent comprehensive performance in terms of mechanical properties, high-temperature aging resistance, fuel resistance, and low-temperature toughness. Among them, Example 2, with the addition of antioxidants and processing aids, shows the best performance, with a tensile strength of 6.8 MPa, an elongation at break of 332%, high performance retention after high-temperature aging, and good resistance to fuel swelling, fully meeting the requirements for use in automotive fuel hoses, intercooler hoses, and air conditioning hoses. The synergistic effect of the ternary fillers, the anti-degradation effect of methyl silicone resin, and the improvement of carbon fiber dispersion by plasma pretreatment are the key factors that make the material's comprehensive performance superior to existing technologies.
[0043] The above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.
Claims
1. A nano-lanthanum oxide-carbon fiber-boron nitride synergistically modified silicone rubber composite material, characterized in that, The modified silicone rubber composite material comprises the following raw material components in parts by weight: 80-100 parts silicone rubber, 2-5 parts nano lanthanum oxide, 3-8 parts carbon fiber, 4-10 parts boron nitride, 3-8 parts methyl silicone resin, 1.1-1.6 parts vulcanizing agent, 1-3 parts coupling agent, and 5-12 parts environmentally friendly plasticizer; The silicone rubber is methyl vinyl silicone rubber, with a vinyl content of 0.08% to 0.16% and a number-average molecular weight of 580,000 to 620,000. The modified silicone rubber composite material also contains 2 to 3 parts of antioxidant, which is a compound mixture of antioxidant NBC and antioxidant 445 or antioxidant D, and antioxidant NBC accounts for 75 to 95% of the total weight of the antioxidant.
2. The nano-lanthanum oxide-carbon fiber-boron nitride synergistic modified silicone rubber composite material according to claim 1, characterized in that, The lanthanum oxide nanoparticles have a particle size of 5–50 nm; the carbon fibers have a length of 50–200 μm and a diameter of 5–15 μm; the boron nitride is hexagonal boron nitride with a particle size of 10–100 nm.
3. The nano-lanthanum oxide-carbon fiber-boron nitride synergistic modified silicone rubber composite material according to claim 1, characterized in that, The coupling agent is one or both of silane coupling agents and titanate coupling agents; the environmentally friendly plasticizer is one or both of environmentally friendly oil and environmentally friendly silicone oil.
4. The nano-lanthanum oxide-carbon fiber-boron nitride synergistic modified silicone rubber composite material according to claim 1, characterized in that, The vulcanizing agent is one or more of 2,4-dichlorobenzoyl peroxide, di-tert-butyl peroxide, 2,5-dimethyl-2,5-bis(tert-butylperoxy)hexane, and dicumyl peroxide.
5. The nano-lanthanum oxide-carbon fiber-boron nitride synergistic modified silicone rubber composite material according to claim 1, characterized in that, Also add 2 to 3 parts of processing aids, wherein the processing aids are one or two of dispersant L-24 and waxy polyethylene.
6. A method for preparing the nano-lanthanum oxide-carbon fiber-boron nitride synergistic modified silicone rubber composite material according to any one of claims 1 to 5, characterized in that, Includes the following steps: (1) Pretreatment: The carbon fiber is plasma treated for 10-30 min, and then mixed with nano lanthanum oxide, boron nitride and coupling agent. The mixture is stirred at 300-500 rpm for 1-2 h at 80-100℃ to obtain the modified filler. (2) Plasticizing: Add silicone rubber to a two-roll mill and plasticize until the Mooney viscosity ML(1+4) at 100°C is 40-60 to obtain the base rubber; (3) Mixing: Transfer the base rubber into an internal mixer, add modified filler, methyl silicone resin, environmentally friendly plasticizer, antioxidant and / or processing aid. The antioxidant and processing aid are mixed at 120-130℃ and 50-120rpm for 5-8 minutes. Adjust the temperature to 100-105℃ and discharge the material. Pass the material through a two-roll mill 3-4 times, and hang the sheet to dry. After standing for 12 hours, add the vulcanizing agent, control the roller temperature of the two-roll mill to not exceed 60℃, the roller gap to 0.5-1.0mm, pass the material through a two-roll mill 4-5 times, and then cool the sheet. (4) Vulcanization: The compound obtained in step (3) is placed on a two-roll mill for re-milling once, and vulcanized for 10-15 min at 160-180℃ and 10-15MPa to obtain nano lanthanum oxide-carbon fiber-boron nitride synergistic modified silicone rubber composite material.
7. The preparation method according to claim 6, characterized in that, In step (1), the power of plasma treatment is 100-300W and the vacuum degree is 0.05-0.09MPa.
8. The application of the nano-lanthanum oxide-carbon fiber-boron nitride synergistic modified silicone rubber composite material according to any one of claims 1 to 5 in the preparation of automotive fuel hoses, automotive intercooler hoses, or automotive air conditioning hoses.
Citation Information
Patent Citations
Antistatic heat conductive rubber and preparation method thereof
CN105199394A
